THE ROLE OF LEAN MANUFACTURING IN ENHANCING OPERATIONAL EFFICIENCY AND WASTE REDUCTION - Suprayitno, Degdo (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The application of Lean Manufacturing has long been recognized as an effective method for increasing operational efficiency and reducing waste in the manufacturing industry. However, in production environments with high variability, there is still a gap in understanding the role of digital technology integration, such as Artificial Intelligence (AI) and the Internet of Things (IoT), in strengthening Lean implementation. This research aims to explore the impact of integrating AI and IoT within a Lean Manufacturing framework on operational efficiency and waste reduction, especially in diverse production conditions. Using a systematic literature review approach with the PRISMA method, data was collected from various international databases, including Scopus and IEEE Xplore. The research results show that the integration of AI and IoT can improve real-time error detection, minimize downtime, and optimize resource utilization more efficiently. These findings provide practical implications for industries facing high variability to adopt digital technologies to strengthen Lean strategies and drive sustainable competitiveness.